A dual-function fluorescent probe for monitoring the degrees of hypoxia in living cells via the imaging of nitroreductase and adenosine triphosphate. Issue 43 (11th May 2018) - Fang, Yu; Shi, Wen; Hu, Yiming; Li, Xiaohua; Ma, Huimin
Abstract : A new dual-function fluorescent probe for nitroreductase and adenosine triphosphate is developed and applied to monitor the degrees of hypoxia in living cells. Abstract : A new dual-function fluorescent probe is developed for detecting nitroreductase (NTR) and adenosine triphosphate (ATP) with different responses. Imaging application of the probe reveals that intracellular NTR and ATP display an adverse changing trend during a hypoxic process and ATP can serve as a new sign for cell hypoxia.